Survey of Basic Technical Skill Levels Football Game on PFA Academy Students Sukoharjo Age Group 13-15 Years - Hamid, Samsul; Waluyo; Adi, Pomo Warih (Java Mutiara Media, 2024)
The purpose of this study was to determine the level of basic technical skills of soccer games in students aged 13-15 years at the PFA Academy Sukoharjo. This research is a quantitative descriptive study using a survey method with data collection using measurement tests, this research seeks to provide an accurate picture of the current technical abilities of students. The subjects of this study were 50 students of PFA Sukoharjo academy age group 13-15 years, and their abilities were assessed through a series of tests measuring dribbling, passing and stopping, and shooting. The results of the data analysis can be displayed as follows: the results of the skill level among the students in the categories of